Al Capone does my shirts - Choldenko, Gennifer, 1957- (New York : Puffin Books, 2006)
A twelve-year-old boy named Moose moves to Alcatraz Island in 1935 when guards' families were housed there, and has to contend with his extraordinary new environment in addition to life with his autistic sister.
Includes bibliographical references.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), March 2007.
Booklist, February 2004.
Keywords: United States Penitentiary, Alcatraz Island, California -- Fiction; United States Penitentiary, Alcatraz Island, California -- Fiction; Autism -- Fiction; Brothers and sisters -- Fiction; Family problems -- Fiction; Historical fiction; Autism -- Fiction; Family problems -- Fiction; Historical fiction; Siblings -- Fiction; Alcatraz Island (Calif.) -- History -- Fiction; Alcatraz Island (Calif.) -- History -- Fiction